Beneficial effects of small-sided games as a conclusive part of warm-up routines in young elite handball players - Iacono, A. D.; Vigotsky, A. D.; Laver, L.; Halperin, I. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to compare the effects of small-sided games (SSGs) and traditional warm-up strategies on the mechanical, physiological, and perceptional responses of handball players. Using a randomized and counterbalanced design, 12 elite male handball players completed a general 8-minute warm-up, which was concluded with an 8-minute section of either specific handball shooting drills or 3 × 2 minutes of 3 vs. 3 SSG with a passive recovery of 1 minute between bouts. Countermovement jumps (CMJs) and plyometric press-ups (PPs) were assessed before and immediately after the warm-up regimens using a force plate. Heart rate (HR) was assessed during the warm-up regimens, and rating of perceived exertion (RPE) was assessed after the regimens. Meaningful differences favoring SSG were observed in most of the kinetic variables in the CMJs and PPs (|Hedges g| = 0.26-1.42). Conversely, no meaningful differences were found between warm-up regimens in RPE or HR responses (z-scores = 0.45 and 1.88, respectively). These results indicate that concluding warm-ups with SSGs offer greater benefits compared with a more traditional warm-up routine, despite similar HR and RPE responses even when matched for duration among elite-level handball players.